Application of LoRa WAN Sensor and IoT for Environmental Monitoring in Riau Province Indonesia - Evizal Abdul Kadir; Akmar Efendi; Sri Listia Rosa (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Land and forest fires especially in Riau Province, Indonesia, have affected the length and breadth of Indonesia. The fires are normally hampered by seasonal dry conditions such as El Nino effect. In addition, the haze has affected the neighboring countries such as Malaysia, Singapore and south of Thailand. The effects of haze on human health as reported in that particular year were about 20 million people have suffered from respiratory problems and serious deterioration in overall health. There were other effects on environment, economy, flora and fauna in Southeast Asia region due to this disaster. This research proposes to develop a smart monitoring system using Long Range Wide Area Network (LoRa WAN) with low power wireless data communication and Internet of Things (IoT) technology. With LoRa technology, data can be transmitted up to 30 miles which is worthwhile to cover some of Riau Province that have been badly impacted by this disaster. In this article propose to develop sensors system that capable of detecting land and forest fire. The sensors will be located at several locations that has badly impacted previously. LoRa IoT Technology will be deployed to provide a platform for connecting the sensors. An early indication of land or forest fires is vital for quick prevention before they become uncontrollable and overwhelming. The design and development of LoRa sensors give high feasibility to overcome current issues in Riau Province because of land and forest fire.